Semi-Empirical Model to Calculate Spray Length Considering Evaporation Effect - Dias Flügel, Alexandre; Zigan, Lars; Schmitz, Ingo; Wensing, Michael; Leipertz, Alfred (23rd Annual Conference on Liquid Atomization and Spray Systems, 2010)
In order to improve air/fuel mixture, fulfilling the European Emission Standard and to reduce fuel consumption, injection and combustion systems have to be improved. The understanding of spray formation and evaporation has been the great challenge of last years in modern gasoline direct-injection (GDI) and Diesel engine as well as aerospace technology. For engine development, the most essential spray data are the cone angle, axial and radial penetration under various injection conditions. The purpose of this work is developing a semi-empiric spray model which is able to predict a single jet penetration of a plain orifice injector, typically from a Diesel or GDI atomizer by different temperatures and pressures based on dimensional analysis theorem. Equations were found to prognosticate the spray penetration and an exponent factor which is able to correct the evaporation effect. The results are satisfactory and the improvement of calculation is possible by adding phenomena such as drag force and air entrainment.<br